The Effect of PROPER Rating and Good Corporate Governance on Carbon Emission Disclosure - Nadhiroh, Hilyatul Aini; Wijayanti, Rita; Ariani, Kurnia Rina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study seeks to investigate the impact of PROPER rating, an independent board of commissioners, and the audit committee on the disclosure of carbon emissions. Methodology : The chosen method for sample selection is purposive sampling, comprising companies not involved in the financial sector that are listed on the Indonesia Stock Exchange from 2020 to 2022, amounting to 516 companies. The data undergoes classical assumption tests and multiple linear regression analysis through the application of IBM SPSS 25. Hypotheses in this study are examined through the F-test and t-test. Results: In summary, the findings of this research indicate that the PROPER rating, company age, and company size have been demonstrated to have an impact on a company's disclosure of carbon emissions. Conversely, factors such as the independent board of commissioners, audit committee, profitability, and leverage do not exert influence on a company's carbon emissions disclosure. Applications/Originality/Value: The occurrence of global warming has led to climate change and a persistent annual increase in temperature. The challenge of addressing global warming has become a focal point of extensive discussions worldwide. This heightened awareness is driving governments to formulate policies aimed at tackling global warming. Consequently, this research is anticipated to serve as a guide for policymakers in establishing regulations that consider the environmental impact while also addressing economic interests.